Self-Directed Learning Attitudes: A Study on English Department Students - Nisa Auliana; Sitti Hadijah (Siliwangi University, 2022)
This research aims to describe the first-year students’ self-directed learning attitudes by employing a descriptive quantitative approach. This study’s population was the second-semester students of the English education department, n=(95), while the sample was selected through a cluster random sampling technique that consists of 55 students. A questionnaire was used to collect the data and distributed online through Google form. The questionnaire adopted from Williamson (2007) comprises five components of self-directed learning; awareness, learning strategies, learning activities, evaluation, and inter-personal skills. The techniques of data analysis involved collecting the data, presenting the data, and interpreting the data. The results showed that 80% of the students are aware of their responsibility in learning. As for learning strategies and activities, 70.91 – 80% of students considered modern educational interactive technology enhance their learning process effectively. There are 60 – 69.09% of the students who applied the self-assess method and are said to monitor their learning progress in terms of evaluation. Regarding their inter-personal skills, most of the students, with a percentage of 83 – 87.27%, are interested in learning about something they frequently exposed to and feel the need to maintain a good interpersonal relationship with others. In conclusion, most of the students, with a percentage of 72.72%, are high self-directed learners with a positive attitude. The attitudes shown by the students are responsible, initiative, independent, curious, and friendly.Keywords: Self-directed learning, Language learning, attitude